Evaluation of in vitro and in vivo release of recombinant human nerve growth factor from bioengineered human stromal lenticule - Lin, Molly Tzu-Yu; Liu, Yu-Chi; Lee, Isabelle Xin Yu; Mandatori, Domitilla; Detta, Nicola; Han, Jing Ying Evelina; Pelusi, Letizia; Mastropasqua, Leonardo; Nubile, Mario; Cattani, Franca; Romeo, Tiziana; Allegretti, Marcello; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSmall incision lenticule extraction (SMILE)-derived lenticules have been repurposed as biocompatible scaffolds to incorporate and release therapeutic substances for ocular therapeutics. We aim to investigate the in vitro and in vivo release profiles of recombinant human nerve growth factor (rhNGF) from bioengineered human stromal lenticules prepared with microparticles incorporated with rhNGF (rhNGF-MPs) for up to 1 and 4 weeks, respectively.MethodsUpon bioengineered lenticule implantation, slit lamp, Anterior Segment Optical Coherence Tomography, and In Vivo Confocal Microscopy were performed to assess corneal biocompatibility, central corneal thickness (CCT), corneal nerve -fiber density (CNFD), -branch density, and -fiber length. Rabbit cornea, tears and aqueous humour were collected to quantify rhNGF release in vivo.ResultsA rapid in vitro release of rhNGF was detected until day 2, and with sustained release over 7 days. The pattern remains comparable even with the presence of antibiotic-antimycotic, trypan blue or fluorescein. Throughout the in vivo follow-up, no signs of corneal haze, edema, infiltration, or pathological increase in CCT were observed. A significant increase in CNFD (p = 0.001) at week 4 was reported in rhNGF-MPs than in Blank-MPs group. Finally, significantly higher NGF content in rabbit cornea and tear was found in rhNGF-MPs group compared to the endogenous NC group (p = 0.035 and p = 0.043, respectively).DiscussionBioengineered lenticules exhibit sustained rhNGF release for at least 7 days in vitro and up to 1 month in vivo. These results, together with absence of adverse effects, and significant increase in CNFD at 4 weeks after lenticule implantation suggest its promising potential for clinical use.